The effects of gender-based differentiated writing instruction on students’ writing skills performance and attitude towards an approach - Belayneh Sugebo; Mebratu Mulatu; Tesfaye Alemu (Social Sciences and Humanities Open)
This study examines the effects of gender-based writing instruction on students' writing performance and their attitudes towards the approach. To examine this, concurrent embedded research design is employed at Hodo Secondary school grade 11 students (21 male and 19 female). From the posttest score result, the study aimed at examining if there is any significant difference in writing skills performance score between male and female students ascribed to gender variable and to identify their attitude towards differentiated writing instruction. To gather sufficient data, writing test, attitude towards differentiated writing instruction questionnaire scale and semi-structured attitude interview were applied before and after intervention. After four months consecutive intervention, Mann-Whitney U test and Wilcoxon Signed Rank tests were used to compute writing skills performance mean rank scores of male and female students and attitude questionnaire scores respectively. Concerning semi-structured interview data analysis, the transcribed data were organized, coded, and categorized into over-arching themes. And their respective major three themes, namely, affective, cognitive and behavioral domains were narrated in words. As a result, there is statistically insignificant difference between writing performance mean rank scores of males and females attributed to gender variable. With respect to the attitude variable, there was statistically significant attitude change from before intervention to after intervention. Its supportive data from semi-structured interview indicated positive attitude towards differentiated writing instruction.